2010
DOI: 10.1111/j.1439-0531.2010.1714.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related Differences in Cytochrome P450 in Porcine Liver – Implication for Activity, Expression and Inhibition by Testicular Steroids

Abstract: In pigs, the hepatic cytochrome P450 (CYP) 1A2, 2A and 2E1 activity is important in the regulation of skatole accumulation in adipose tissue. This study investigated gender-related differences in CYP1A2, 2A and 2E1 dependent activity, protein and mRNA expression. This study also investigated the gonadal steroid dependent inhibition of CYP activity in relation to gender and dietary composition. Microsomes were prepared from the liver of female and entire male pigs (Landrace × Yorkshire sire and Duroc boars) rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 35 publications
2
57
1
2
Order By: Relevance
“…It is known that the levels of enzymes that are involved in the degradation of skatole (CYP2E1 and CYP2A) are increased in barrows and immunocastrates when compared with the levels in boars (Zamaratskaia et al, 2009;Brunius et al, 2012). In vitro studies with porcine hepatocytes revealed that the addition of androstenone in physiological amounts reduced the activity of both enzymes (Doran et al, 2002b;Rasmussen et al, 2011). Such mechanisms may contribute to lower skatole concentrations in adipose tissue of immunocastrated than in boars, as found in this study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is known that the levels of enzymes that are involved in the degradation of skatole (CYP2E1 and CYP2A) are increased in barrows and immunocastrates when compared with the levels in boars (Zamaratskaia et al, 2009;Brunius et al, 2012). In vitro studies with porcine hepatocytes revealed that the addition of androstenone in physiological amounts reduced the activity of both enzymes (Doran et al, 2002b;Rasmussen et al, 2011). Such mechanisms may contribute to lower skatole concentrations in adipose tissue of immunocastrated than in boars, as found in this study.…”
Section: Discussionsupporting
confidence: 64%
“…Such mechanisms include an increased formation rate due to higher amounts of intestinal cell debris stimulated by endocrine or nutritional factors (Claus et al, 1996). Moreover, sex differences in hepatic skatole metabolism due to a specific inhibitory effect of androstenone on hepatic skatole degradation (Babol et al, 1999;Doran et al, 2002a and2002b;Rasmussen et al, 2011) have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of mRNA, reverse transcription and PCR were performed as described by Rasmussen et al (2011d). Briefly, from approximately 10 mg frozen liver tissue, mRNA was isolated using an RNA isolation kit (RNeasy Mini Kit, VWR, Herlev, Denmark) and converted to cDNA by the use of SuperScript II RNase H Reverse Transcriptase and Oligo(dT)12-18 primer (Invitrogen, Carlsbad, CA, USA), according to the manufacturer's instructions.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…The mRNA content of the samples was assessed using PCR with specific primers and a TaqMan probe. Sequences of the primers and probes used were described by Rasmussen et al (2011d). Relative mRNA expression was calculated from the obtained Ct values and normalised against mRNA expression of glyceraldehyde-3-phosphate dehydrogenase.…”
Section: Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation